GDT309 : Major discipline / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
A comprehensive graphic design course which allow student to pursue their main area of interest in graphic design speacialized areas. This course will equipt student with greater understanding and appreciation of contemporary graphic design realm. In this advance design practise course,the student are guided to find a new way in their creative look without ignoring the basic principles. There are 4 (four) sets of comprehensive assignment to be covered: 1) Brand Identity Design/ Corporate Identity Design - Identity Design - Type Design & Lettering - Packaging Design 2) Advertising - Advertising Design & Art Direction - Promotional Design - Supporting Marketing Tools 3) Illustration - Graphic Illustration 2D/ 3D - Manual Illustration Publication Design 4) Multimedia - Web Interface Design - Animation 2D/ 3D - TV Commercial - Cor porate Video - Video Montage a) Identity Design b) Information design c) Promotional design d) Publication Design e) Type Design and Lettering f) Graphic Illustration 2D/3D g) Advertising h) Interface Design i) Animation 2D/3D The need of central review should be organize frequently combined with all campuses (Graphic Design & Media Digital Department) to ensure the quality of project produced by students in every campuses meet the standard and requirements.